(untitled) (Oxford, 2006)
Contents of the book inculude 5 section: Physical examination, diagnosis, and body systems; Viral diseases; Bacterial diseases; Miscellaneous conditions; Veterinary practice
Thâm cứu bệnh nhiệt đới,Thâm cứu bệnh học thú y,Bệnh truyền lây giữa người và động vật
Keywords: Swine,Bệnh heo; Diseases